2012
DOI: 10.1186/1471-2458-12-58
|View full text |Cite
|
Sign up to set email alerts
|

Psychological characteristics in high-risk MSM in China

Abstract: BackgroundMen who have sex with men (MSM) have become a high-risk group of HIV infection in China. To date, little is known regarding the behavioral, social and psychological characteristics in Chinese MSM, which makes the implementation of preventive and therapeutic strategies for this high-risk subpopulation of people extremely difficult.MethodsA total of 714 questionnaires were retrieved from the database of a Chinese government-sponsored National Key Research Project titled "Risk Analysis and Strategic Pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 20 publications
0
24
0
Order By: Relevance
“…Previous studies have shown that higher education and self-perceived risk for HIV are positively correlated with history of HIV testing (Han et al, 2014; Xun et al, 2013). Further, in China close to one-half of MSM are likely to be married (Chen et al, 2012). Married MSM are more likely to have had sex with women and may be more reluctant than single MSM to access HIV testing due to fear of sexuality disclosure (Bien et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that higher education and self-perceived risk for HIV are positively correlated with history of HIV testing (Han et al, 2014; Xun et al, 2013). Further, in China close to one-half of MSM are likely to be married (Chen et al, 2012). Married MSM are more likely to have had sex with women and may be more reluctant than single MSM to access HIV testing due to fear of sexuality disclosure (Bien et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The global literature, including the limited number of studies in China, suggests that alcohol use and abuse are positively associated with a number of risky sexual behaviors and outcomes such as unwanted pregnancy and sexually transmitted infections (STIs) including HIV and syphilis (10)(11)(12)(13)(14)(15)(16)(17)(18)(32)(33)(34)(35). However, these studies often examine global instead of temporal (i.e., sex after drinking) associations.…”
Section: Discussionmentioning
confidence: 99%
“…HIV-related stigma is one of the strongest determinants of psychological problems (e.g., depression) among MSM [17, 18] and PLWH in China [19]. High levels of stigma and discrimination experienced by PLWH has been well documented [20].…”
Section: Introductionmentioning
confidence: 99%